Efficacy of the neurokinin‐1 receptor antagonist aprepitant in children with cyclical vomiting syndrome. Issue 3 (5th June 2014) - Cristofori, F.; Thapar, N.; Saliakellis, E.; Kumaraguru, N.; Elawad, M.; Kiparissi, F.; Köglmeier, J.; Andrews, P.; Lindley, K. J.; Borrelli, O.
Summary Background Aprepitant (Emend, Merck Sharp & Dohme Ltd, Haarlem, the Netherlands), a neurokinin‐1 receptor antagonist, prevents vomiting in a range of conditions. No data are available on its use in children with cyclical vomiting syndrome (CVS). Aim We investigated the efficacy of aprepitant as prophylactic treatment or acute intervention in CVS children refractory to conventional therapies. Methods Forty‐one children (median age: 8 years) fulfilling NASPGHAN criteria treated acutely (RegA) or prophylactically (RegP) with aprepitant were retrospectively reviewed. Primary outcome was the clinical response (decrease in frequency and intensity of CVS episodes). Secondary outcomes were: number of CVS episodes/year, number of hospital admissions/year, CVS episode duration, number of vomits/h, symptom‐free interval length (days), and school attendance percentage. The follow‐up period was 18–60 months. Results Sixteen children received RegP and 25 RegA. One child on RegP stopped treatment due to severe migraine. At 12‐months on intention‐to‐treat analysis, 13 children on RegP (81%) achieved either complete (3/16, 19%) or partial (10/16, 62%) clinical response. On RegA, 19 children (76%) had either complete (3/25, 12%) or partial (16/25, 64%) response (P = 0.8 vs. RegP). In both RegP and RegA, there was a significant decrease in CVS episodes/year, hospital admission number/year, CVS episode length, number of vomits/h, as well as an increase in symptom‐free interval duration and school attendance percentage. Side effects were reported only in RegP (5/16, 31%) including hiccough (3/16, 19%), asthenia/fatigue (2/16, 12.5%), increased appetite (2/16, 12.5%), mild headache (1/16, 6%) and severe migraine (1/16, 6%). Conclusion Aprepitant appears effective for both acute and prophylactic management of paediatric cyclical vomiting syndrome refractory to conventional therapies.